Flow alterations by dams shaped fish assemblage dynamics in the complex Mekong-3S river system. (May 2018) - Ngor, Peng Bun; Legendre, Pierre; Oberdorff, Thierry; Lek, Sovan
Highlights: Hydrology spatially and temporally structures local and regional fish assemblages. Flow disruptions by dams alter temporal fish assemblage composition dynamics. Flow regulation decreases species diversity and mutes fish assemblage seasonality. Unpredictable flows by dams homogenize fish faunas and favor generalist species. Knowledge about flow and fish responses are vital for fish conservation planning. Abstract: The Mekong, Sekong, Sesan, and Srepok (Mekong-3S) river system, a Ramsar wetlands of international importance and critical fish migration routes, is altered by dams that distort the seasonal flow dynamics, structuring dispersal and reproduction success of fishes. Here, we investigate the temporal responses of local fish beta diversity to hydrologic modification by the upstream functioning dams in five sites of the Mekong-3S system. The sampling design adopted (two sites on the Mekong River displaying relatively undisturbed flow and three sites in the 3S displaying a gradient in flow perturbation) allows us to focus on the effect of flow alteration on local fish assemblage compositions. By analysing 7-year daily fish monitoring data (06/2007–05/2014), we found that there have been overall declining trends in local species richness and abundance, with strong temporal variability in local beta diversity. Undisturbed sites are characterized by seasonal assemblage variability, while disturbed sites are characterized by aseasonal assemblage changes. Temporal shifts in assemblage composition suggest that dams alter seasonal flow patterns and favour generalist species. This study contributes to a better understanding of the temporal changes of tropical freshwater fish beta diversity in regulated and unregulated rivers. It is thus relevant for fisheries planning and conservation.